2020
DOI: 10.1111/bcp.14179
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate and postgraduate pharmacovigilance education: A proposal for appropriate curriculum content

Abstract: Background Adverse drug reactions (ADRs) are common, often preventable, and a leading cause of morbidity and mortality. Pharmacovigilance (PV) involves detection, assessment, understanding, and prevention of adverse effects or any other drug‐related problem. Education of healthcare professionals (HCPs) involved in drug prescription, dispensing and administration is essential to help prevent and mitigate both ADRs and medication errors and has to be focused on 3 pivotal aspects: •Awareness: All medicines can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Therefore, we would recommend that other healthcare curricula (medicine, pharmacy, or nursing) incorporate this simple reallife, problem-and context-based pharmacovigilance educational intervention as it fits perfectly into the proposed curriculum. [21] Further research is needed to analyze whether a shorter version of the reporting assignment will further encourage ADR reporting. Although our findings are encouraging, reporting rates were limited by "Excuses made by professionals", an aspect not adequately addressed in our educational intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we would recommend that other healthcare curricula (medicine, pharmacy, or nursing) incorporate this simple reallife, problem-and context-based pharmacovigilance educational intervention as it fits perfectly into the proposed curriculum. [21] Further research is needed to analyze whether a shorter version of the reporting assignment will further encourage ADR reporting. Although our findings are encouraging, reporting rates were limited by "Excuses made by professionals", an aspect not adequately addressed in our educational intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent literature review showed an urgent need for more innovative learning initiatives in pharmacovigilance training [20] and a recent study stressed the use of clinical and real-life continuing learning initiatives. [21] It also advised studying the long-term effects and clinical value of educational initiatives. [20].…”
Section: Introductionmentioning
confidence: 99%
“…Complementing these WHO curricular recommendations, Herrera-Comoglio further proposed basic and advanced ADR education contents to be taught in both undergraduate and postgraduate settings (Table 3) [59].…”
Section: Adr Education Curriculummentioning
confidence: 99%
“…Topics and content of adverse drug reaction education curriculum[59] ADR adverse drug reaction, ALDEN Algorithm for Assessment of Drug Causality in Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis, Regi-SCAR Registry of Severe Cutaneous Adverse Reaction, WHO World Health Organization…”
mentioning
confidence: 99%
“…After a drug reaches the drug market, it is necessary to regularly evaluate its safety profile (post-marketing surveillance) and assess the ADRs associated with it because only the most prevalent ADRs are found during pre-marketing trials. 6 As a result, developing strategies for quickly recognizing and monitor ADR and other post-marketing post-marketing surveillance activities is critical. 7 The purpose of this study was to determine the prevalence of ADRs and associated factors among patients on psychotropic medications at Mizan Tepi University Teaching Hospital (MTUTH).…”
Section: Introductionmentioning
confidence: 99%